A Case of Carbamazepine-Induced Aggravation of Self-Limited Epilepsy with Centrotemporal Spikes Epilepsy and Valproate-Induced Hyperammonemic Encephalopathy in a Child with Heterozygous Gene Variant of Carbomoyl Phosphatase Synthetase Deficiency. (31st December 2021) - Kankananarachchi, Imalke; Jasinge, Eresha; Hewawitharana, Gemunu
Abstract : Antiepileptics drugs are the mainstay of the management of epilepsy in children. Sodium valproate (VPA) and carbamazepine (CBZ) are widely used medications in childhood epilepsy. Hyperammonemia has been described as a known side effect of valproate therapy. It is known that VPA-associated HA is common among patients who hold genetic mutations of the carbomoyl phosphatase synthase 1 gene (CPS1). Aggravation of self-limited epilepsy with centrotemporal spikes (SLECTS) is a rare side effect of CBZ. Here, we present a child who had CBZ-induced aggravation of rolandic epilepsy and VPA-induced HA encephalopathy in the background of an unrecognised heterozygous gene variant of CPS1. An 8-year-old boy with SLECTS presented with a history of abnormal behaviours and drowsiness. He was apparently well until six years when he developed seizures in favour of rolandic epilepsy. His electroencephalogram (EEG) showed bilateral predominantly on the right-sided central-temporal spikes and waves. The diagnosis of SLECTS was made, and he was commenced on CBZ. Though he showed some improvement at the beginning, his seizure frequency increased when the dose of CBZ was increased. His repeat EEG showed electrical status in slow-wave sleep, and CBZ was stopped. Subsequently, he was started on VPA, and with that, he developed features of encephalopathy. He had elevated serum ammonia with normal liver functions. VPA was stopped with the suspicion of VPA-induced hyperammonemia. Tandem mass spectrometry did not show significant abnormality in the amino acid profile. Specific genetic analysis revealed a c.2756 C > T.p (Ser919Leu) heterozygote genetic mutation of the CSP 1 gene. This is a classic example where side effects of treatment determine the choice of antiepileptics drugs (AEDs) in childhood epilepsy. It is essential to keep in mind that SLECTS can be aggravated with certain AEDs, and VPA-induced HA in the absence of live failure could be due to underlying inherited metabolic disorders.